Thermal Analysis, Structural Studies and Morphology of Spider Silk-like Block Copolymers. - Huang, Wenwen. (2017)
Abstract: Spider silk is a remarkable natural block copolymer, which offers a unique combination of low density, excellent mechanical properties, and thermal stability over a wide range of temperature, along with biocompatibility and biodegrability. The dragline silk of Nephila clavipes, is one of the most well understood and the best characterized spider silk, in which alanine-rich hydrophobic blocks and glycine-rich hydrophilic blocks are linked together generating a functional block copolymer with potential uses in biomedical applications such as guided tissue repair and drug delivery. To provide further insight into the relationships among peptide amino acid sequence, block length, and physical properties, in this thesis, we studied synthetic proteins inspired by the genetic sequences found in spider dragline silks, and used these bioengineered spider silk block copolymers to study thermal, structural and morphological features. To obtain a fuller understanding of the thermal dynamic properties of these novel materials, we use a model to calculate the heat capacity of spider silk block copolymer in the solid or liquid state, below or above the glass transition temperature, respectively. We characterize the thermal phase transitions by temperature modulated differential scanning calorimetry (TMDSC) and thermogravimetric analysis (TGA). We also determined the crystallinity by TMDSC and compared the result with Fourier transform infrared spectroscopy (FTIR) and wide angle X-ray diffraction (WAXD). To understand the protein−water interactions with respect to the protein amino acid sequence, we also modeled the specific reversing heat capacity of the protein-water system, Cp(T), based on the vibrational, rotational and translational motions of protein amino acid residues and water molecules. Advanced thermal analysis methods using TMDSC and TGA show two glass transitions were observed in all samples during heating. The low temperature glass transition, Tg(1), is related to both the bound water removal induced conformational change and the hydrophobicity of the protein sequences, while the high temperature glass transition, Tg(2), above 130 °C is the now dry protein glass transition. Real-time Fourier transform infrared spectroscopy (FTIR) confirmed that conformational change occurred during the two glass transition, with a random coils to beta turns transition during Tg(1) and alpha helices to beta turns transition during Tg(2). Due to the hydrophobic and hydrophilic nature of the blocks, the spider silk block copolymers tend to self-assemble into various microstructures. To study the morphological features, the spider silk-like block copolymers were treated with hexafluoroisopropanol or methanol, or subjected to thermal treatment. Using scanning electron microscopies, micelles were observed in thermally treated films. Fibrillar networks and hollow vesicles were observed in methanol-cast samples, while no micro-structures were formed in HFIP-cast films, indicating that morphology and crystallinity can be tuned by thermal treatments. Results indicate when we increase the number of repeating unit of A-block in the protein, sample films crystallize more easily and are more thermally stable. Moreover, when samples crystallize, the secondary structure of A-block and B-block become different, thus it will be easier to form bilayer structures which could fold into vesicles or tube structures during drying.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Physics.; Advisor: Peggy Cebe.; Committee: Roger Tobin, Cristian Staii, Gary Goldstein, and Christoph Schick.; Keywords: Physics, and Biomedical engineering.